The fever on the farm - Grace, Delia (American Association for the Advancement of Science, 2015)
At the turn of the twentieth century, innovations in agriculture and infrastructure created opportunities for livestock diseases to emerge and spread in the United States. Arresting Contagion offers a penetrating glimpse into the behavioral economics that defined early animal disease control efforts, a story complete with setbacks and victories, heroes and villains. Reviewer Delia Grace applauds this comprehensive history, and recommends it those who are grappling with the resurgence in zoonotic diseases brought about by the rapid expansion of the livestock sector in developing countries and elsewhere.